2016
DOI: 10.1017/s0950268816002119
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal carriage in children and young adults in the Philippines: a single group, cross-sectional study

Abstract: SUMMARYThis cross-sectional prevalence study investigates meningococcal carriage for the first time in a Southeast Asian population. Posterior pharyngeal swabs were collected between August 2013 and March 2014 from 937 healthy Filipinos aged 5-24 years attending school or university in Manila. Of these, 35 were found to be carriers giving an overall carriage prevalence of 3·7% [95% confidence interval (CI) 2·6-5·2]. Carriage was associated with age (P < 0·001) and was highest (9·0%, 95% CI 5·5-13·8) in subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Although practices vary, chemoprophylaxis is commonly prescribed, with immunization only being recommended for those in high-risk groups. 24 These groups may include people with complement deficiencies, human immunodeficiency virus (HIV), or those attending a pilgrimage or a mass gathering in another country/region. Such recommendations are promoted in Vietnam, the Philippines, New Zealand, Thailand, Taiwan, Singapore and Indonesia.…”
Section: Serogroup Distributionmentioning
confidence: 99%
“…Although practices vary, chemoprophylaxis is commonly prescribed, with immunization only being recommended for those in high-risk groups. 24 These groups may include people with complement deficiencies, human immunodeficiency virus (HIV), or those attending a pilgrimage or a mass gathering in another country/region. Such recommendations are promoted in Vietnam, the Philippines, New Zealand, Thailand, Taiwan, Singapore and Indonesia.…”
Section: Serogroup Distributionmentioning
confidence: 99%
“…Currently, low and middle income countries in Asia do not have routine and robust IMD surveillance programs; therefore, disease burden and at-risk populations are not well elucidated [19,48]. In addition, few countries in the region currently include meningococcal vaccines in their national immunization programs (Table S1) [24].…”
Section: Surveillance Disease and Vaccinationmentioning
confidence: 99%
“…1). Of these, nine met the inclusion criteria and were included in the review, including two studies from China [51,53], three from India [54][55][56], and one each from Malaysia [57], Nepal [58], the Philippines [48], and Thailand [59] (Fig. 3; Table 3).…”
Section: Literature Search Findings On Carriage In Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that have assessed the prevalence of carriage within specific countries/populations show remarkable differences. For instance, in a study carried out on university students in the UK during the winter of 2009/2010, it was found that carriage rates could reach 55% [ 17 ]; another recent study in the UK shows carriage rates from 3.9 to 26.5% in students aged 10–25 [ 18 ]; while carriage in children and young adults in The Philippines ranged, according to age, from less than 3% to 9% [ 19 ]. In Chile, a previous study performed in university students has revealed a lower carriage rate compared to European countries (4% in a cohort of 500 students] [ 20 ], a result that was attributed to our educational system lacking massive student residences.…”
Section: Introductionmentioning
confidence: 99%